The potential benefits and challenges of agricultural animal biotechnology to pastoralists - Loquang, T.M.; Köhler-Rollefson, Ilse (TSAP and ILRI, 2006)
The livelihoods of pastoralists revolve around their indigenous livestock. Combining high production with disease resistance using genetic engineering is a biotechnological intervention hailed by some as a promising avenue to mitigate food insecurity and poverty. Considerable human and financial resources have already been devoted to exploring this option. However, the challenges are enormous. It is unlikely that such livestock would survive in the harsh ecosystems where pastoralists live and that it would meet their diverse and breed specific social and economic requirements. Furthermore, the questions of intellectual property rights over genetically engineered livestock need to be resolved otherwise there is the danger of the genetic traits of indigenous livestock being pirated by industrial breeders. The loss of biodiversity and of pastoralist livelihoods might also be possible consequences. Instead of genetically engineered livestock, pastoralists need recognition of their livestock breeds and management skills, the right to their own breeding decisions and improved services to enhance their livelihood and support their breeds.